Theoretical preconditions of vocational training the future teacher of music - V.M. Semenyak (Academy of Cognitive and Natural Sciences, 2006)
In article mechanisms of preparation the future teacher of music to performing activity are analysed; stages of preparation for this activity are isolated; the contents of. a method ofauto-training is opened.